"Makes Me Wanna Holler": Refuting the "Culture of Poverty" Discourse in Urban Schooling. Issue 1 (September 2017) - Ladson-Billings, Gloria
A common explanation of why urban students fail to succeed in the classroom is that they are coming from a "culture of poverty." This article argues that urban students, particularly those who are African American, face a series of structural and institutional barriers that impede their pathways to success. Lack of access to quality healthcare, affordable housing, and quality schools means that the nation's most disadvantaged children remain disadvantaged. Yet classrooms with highly qualified teachers who believe in the efficacy of their practice and the ability of all students to learn can make a difference in these children's lives.